Quantifying the Relationship between Capability and Health in Older People: Can't Map, Won't Map. (January 2018) - Franklin, Matthew; Payne, Katherine; Elliott, Rachel A.
Background. Intuitively, health and capability are distinct but linked concepts. This study aimed to quantify the link between a measure of health status (EQ-5D-3L) and capability (ICECAP-O) using regression-based methods.Methods. EQ-5D-3L and ICECAP-O data were collected from a sample of older people ( n = 584), aged over 65 years, requiring a hospital visit and/or care home resident, and recruited to one of 3 studies forming the Medical Crisis in Older People (MCOP) program in England. The link of EQ-5D-3L with 1) ICECAP-O tariff scores were estimated using ordinary least squares (OLS) or censored least absolute deviation (CLAD) regression models; and 2) ICECAP-O domain scores was estimated using multinomial logistic (MNL) regression. Mean absolute error (MAE), root mean squared error (RMSE), absolute difference (AD) between mean observed and estimated values, and the R 2 statistic were used to judge model performance.Results. In this sample of older people ( n = 584), higher scores on the EQ-5D-3L were shown to be linked with higher ICECAP-O scores when using linear regression. An OLS-regression model was identified to be the best performing model with the lowest error statistics (AD = 0.0000; MAE = 0.1208; MSE = 0.1626) and highest goodness of fit ( R 2 = 0.3532); model performance was poor when predicting the lower ICECAP-O tariff scores. The three domains of the EQ-5D-3L showing a statistically significant quantifiable link with the ICECAP-O tariff score were self-care, usual activities, and anxiety/depression.Conclusion. A quantifiable, but weak, link between health (EQ-5D-3L) and capability (ICECAP-O) was identified. The findings from this study add further support that the ICECAP-O is providing complimentary information to the EQ-5D-3L. Mapping between the 2 measures is not advisable and the measures should not be used as direct substitutes to capture the impact of interventions in economic evaluations.